Classification and Mass Measurement of Nuts Using X-ray Images - Coker, Mustafa; Akgul, Yusuf Sinan (IEEE, 2013)
The current practices for the agricultural inspection of the nuts do not produce satisfactory results. It is argued that the quality standards in this field can be greatly improved by using quantitative data. This paper proposes using X-Ray images of nuts for the objective assessment of the fruit mass and quality. X-Ray images produce data that indicates the density of the nuts which is valuable in this assessment. This data is used with a set of novel computer vision methods for the classification and the mass measurement of nuts. The experiments performed on the data indicate good performance of the results and usability of the proposed system in the real life.
21st Signal Processing and Communications Applications Conference (SIU) -- APR 24-26, 2013 -- CYPRUS
Keywords: Nuts; X-ray; classification; mass measurement; decision tree; regression